ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP PEMILIHAN METODE DEPRESIASI UNTUK AKTIVA TETAP PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK JAKARTA - Muhammad Nuryatno; Nazmel Nazir; Ramaditya Adinugraha (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2007)
The objective of this thesis is to identify the influence of firm's size, leverage ratio, and accounting ROA to the depreciation method selection for plant assets in manufacturing companies listed in Jakarta Stock Exchange. The dependent variabel in this research is depreciation method selection, which is measured by nominal scale, while, the independent variables consists firm's size, leverage ratio, and accounting ROA is measured by metric scale. The data in this research includes 55 manufacturing companies which were selected by using a purposive judgement sampling in the period of 2002 until 2005. The method used in this research are normality test, classic assumption, and hypotheses test by using logistic regression analysis. The result of this research is that at the alpha rate of 5%, each of the independent variables -including firm's size, leverage ratio, and ROA- do not have significant influences to the depreciation method selection for plant assets in the manufacturing companies listed in Jakarta Stock Exchange. Meanwhile, a simultaneous test performed to theese three independent variables doesn't show a result of significant influence to the depreciation method selection for plant assets in those companies neither.